Electrospun Rare-Earth Metal Oxide (CeO2 ) Nanofiber for the Degradation of Congo Red Aqueous Dyes - Rianjanu, Aditya; Haloho, Trivendi; Pasaribu, Joshua Leonardo; Fahmi, Achmad Gus; Nurfani , Eka; Sipahutar, Wahyu Solafide; Yudistira, Hadi Teguh; Taher, Tarmizi (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2025)
The persistent presence of organic dyes like Congo Red (CR) in wastewater poses a significant environmental challenge. In this study, CeO2 nanofibers (CeO2-NF) were successfully synthesized via electrospinning followed by calcination as potential photocatalysts for the degradation of CR pollutants in aqueous solutions. The synthesized nanofibers were characterized using field emission scanning electron microscopy coupled with energy dispersive X-Ray Spectroscopy (FESEM-EDS) for morphological and elemental analyses, X-Ray Diffraction (XRD) for crystalline structure, and Fourier transform infrared (FTIR) spectroscopy for molecular properties. Photocatalytic degradation experiments were conducted under UVC light irradiation, with the CeO2-NF1, CeO2-NF2, and CeO2-NF3 samples achieving CR degradation percentages of 95.6%, 96.9%, and 95.2%, respectively, after 130 minutes of reaction time. Kinetic analysis revealed that the photocatalytic degradation followed pseudo-first-order kinetics, with rate constants of 0.020 min-1, 0.024 min-1, and 0.025 min-1 for CeO2-NF1, CeO2-NF2, and CeO2-NF3, respectively, highlighting the superior performance of CeO2-NF3. These results indicate that CeO2NF could serve as an effective material for the photocatalytic degradation of organic dyes, offering a promising approach for wastewater treatment applications.